Production and application of ceramovermiculite materials based on layered vermiculite in Uzbekistan (Международный научный журнал «Инженер», 2026)
The results of a study on the influence of serpentinite on the properties of ceramovermiculite arepresented. The introduction of a natural magnesium-containing material into the mixture increases thestrength of the samples while decreasing shrinkage and density. The combined addition of serpentinite,coal (as a combustible additive), and nepheline made it possible to obtain ceramovermiculite materialswith high thermophysical properties